A Branchial Cyst in a Diamond Python (Morelia spilota). (November 2019) - Cloup, E.; Thomas, C.; Cooper, J.E.
Summary: A 9-year-old female diamond python ( Morelia spilota ) was presented with a submandibular swelling. The cytological, macroscopic and histological features of this lesion indicated a diagnosis of branchial (pharyngeal) cyst. Branchial cysts are benign lesions caused by anomalous development of the branchial apparatus and are described rarely in veterinary medicine. We suggest that possible persistence of branchial remnants should be included in the consideration of differential diagnoses for neck masses in adult snakes.